1998
DOI: 10.1080/07315724.1998.10718813
|View full text |Cite
|
Sign up to set email alerts
|

Lactose Intolerance and Self-Reported Milk Intolerance: Relationship with Lactose Maldigestion and Nutrient Intake

Abstract: In studies of the general population, the frequency of lactose intolerance is much lower than that of lactose maldigestion. Gastrointestinal symptoms after lactose load in self-reported milk-intolerants are found in only a very low number of these subjects. Furthermore, in these subjects we observed an unnecessary reduction in milk consumption and an insufficient dietary calcium intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
69
1
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 24 publications
8
69
1
5
Order By: Relevance
“…This is in line with other studies [6,8,9] showing that not all individuals with lactose malabsorption report symptoms from food containing lactose. T he colonic micro biota is variable [28] and the individual sensitivity to feel distension of the colon and to sense discomfort varies [29] .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This is in line with other studies [6,8,9] showing that not all individuals with lactose malabsorption report symptoms from food containing lactose. T he colonic micro biota is variable [28] and the individual sensitivity to feel distension of the colon and to sense discomfort varies [29] .…”
Section: Discussionsupporting
confidence: 81%
“…celiac disease [3] . Cases of individuals suspecting they have lactose intolerance are more common than the true prevalence of adult-type hypolactasia [4][5][6][7][8][9] . It has been shown that lactose-restricted diets improve symptoms markedly for example in IBS patients with lactose malabsorption and reduce the number of visits to the outpatient clinics [10] .…”
Section: Introductionmentioning
confidence: 99%
“…However, calcium utilization depends upon individual factors, such as the lactase-deficiency degree as well as on food characteristics [30]. Thus, several studies have shown that yoghurt is better tolerated than milk [11], because some lactase activity from yoghurt bacteria could participate in lactose digestion, as well as the delayed oro-cecal transit time [23,31].…”
Section: Discussionmentioning
confidence: 99%
“…They are the biggest source of Ca in the Australian diet and whole milk and other dairy foods provide a unique package of other essential nutrients including protein, vitamins (A, B 12 and riboflavin) and minerals (P, Mg, K and Zn) (1) . Not consuming these foods risks insufficient dietary Ca intake and has been known to result in reduced bone mineral density, increased incidence of fracture, and other risks to health and well-being (1)(2)(3) .…”
mentioning
confidence: 99%